Responding to the Needs of Early Career SETs through Educator Preparation Programs - Jeongae Kang; Shantel Farnan; Tamara Lynn (The Advocate, 2018)
Effective collaboration between special education teachers (SETs) and general educator teachers (GETs) is critical to better serve diverse students in the general education classroom. However, multiple areas of needs reported by early career SETs indicate that achieving the goal of effective collaboration is challenging. With a better understanding of the early experiences of SETs and their specific needs, GETs would be more suited to support early career SETs and increase effective partnerships across diverse educational settings. This article identified the needs of beginning SETs and discussed the directions of educator preparation programs in response of the reported needs.
Keywords: collaboration; early career special education teachers; general education teachers; educator preparation program